PERSEPSI TENTANG RISIKO BREAKTHROUGH INFECTION COVID-19 DALAM LINGKUNGAN HEALTH RISK MESSAGES - Tandiyo Pradekso; Djoko Setyabudi (KINESIK, 2021)
The Covid-19 vaccination rate continues to increase, it is important to pay attention to the possibility of a breakthrough infection, which is a viral infection that occurs after a person has been vaccinated. This is a case that is expected to occur in some of those who have received the vaccine, as no vaccine for any disease is 100 percent effective. During the time of living in this period of the Covid-19 pandemic, people are always exposed to information about the dangers or threats of exposure to the virus, known as health risk messages. This study was conducted to explain how a number of individual characteristics in the health risk message information environment correlate to their attitudes towards the risk of exposing Covid-19. This online survey of people who have received the Covid-19 vaccine found that several variables related to lifestyle and disease history were correlated to perceptions of the risk of exposure to Covid-19. It also confirms that there is a positive correlation between awareness of the amount of risk an individual has and perceptions of the risk of exposing Covid-19.